Proceedings of the 20th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2014
DOI: 10.1145/2623330.2623637
|View full text |Cite
|
Sign up to set email alerts
|

Streaming submodular maximization

Abstract: How can one summarize a massive data set "on the fly", i.e., without even having seen it in its entirety? In this paper, we address the problem of extracting representative elements from a large stream of data. I.e., we would like to select a subset of say k data points from the stream that are most representative according to some objective function. Many natural notions of "representativeness" satisfy submodularity, an intuitive notion of diminishing returns. Thus, such problems can be reduced to maximizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Here, on the other hand, we present guaranteed approximation results for all monotone and non-monotone submodular functions. In fact, Ashwinkumar and Karbasi [6] observed that if one applies the greedy algorithm without a consistent tie-breaking rule, the approximation factor of the algorithm is not bounded for coverage functions. In this paper, we prove that a class of algorithms including greedy with a consistent tie-breaking rule provide a guaranteed 0.27-approximation algorithm for all monotone submodular functions.…”
Section: Other Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, on the other hand, we present guaranteed approximation results for all monotone and non-monotone submodular functions. In fact, Ashwinkumar and Karbasi [6] observed that if one applies the greedy algorithm without a consistent tie-breaking rule, the approximation factor of the algorithm is not bounded for coverage functions. In this paper, we prove that a class of algorithms including greedy with a consistent tie-breaking rule provide a guaranteed 0.27-approximation algorithm for all monotone submodular functions.…”
Section: Other Related Workmentioning
confidence: 99%
“…We can increase the value of a * j by c * j , and then set c * j to zero. This update keeps a * j + c * j intact, and therefore does not change anything in constraints (1), ( 3), ( 5), and (6). It also makes it easier to satisfy constraint (2) since it (possibly) reduces the right hand side, and keeps the left hand side intact.…”
Section: Claim 47mentioning
confidence: 99%
“…Monotone k-submodular Nguyen and Thai (2020) generalize the threshold greedy approach of Badanidiyuru et al (2014) to k-submodular maximization under a common cardinality constraint of size r, that works by guessing the value of the optimum solution. Their method achieves a near-optimal 1 2 − ϵ approximation, but keeps multiple solutions in memory, which requires space O( r log r ϵ ) and is not suited for the online setting.…”
Section: Additional Related Workmentioning
confidence: 99%
“…[1][2][3][4] The other one is the constraints on the solution. At present, cardinality constraint, [5][6][7] matroid constraint, 8-10 p-system constraint, 11,12 and knapsack constraint [13][14][15] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%